Computational thermodynamics and kinetics-guided re-engineering of a high-performance tool steel. (15th July 2023) - Zhou, Tao; Spartacus, Gabriel; Dahlström, Alexander; Babu, R. Prasath; Davydok, Anton; Hedström, Peter
Abstract: Targeting to obtain fine dispersions of nanoscale precipitates to enhance the mechanical properties of a high-performance tool steel, re-engineering of the alloy composition and heat treatment was guided by computational thermodynamics and kinetics. A prototype alloy was prepared using the designed chemistry and heat treatment. Thereafter, advanced microstructural characterization and mechanical testing confirmed the successful design to reach a high number density of (V, Mo)C precipitates with an average diameter of about 5 nm in the peak-hardened condition, after tempering the martensite at 600 °C for 2 h. Graphical abstract: Image, graphical abstract